2013
DOI: 10.1021/ie401442t
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Isoflavones from the Soy Whey Wastewater Using Two-Stage Batch Foam Fractionation

Abstract: The feasibility of recovering bioactive substances without surface activity from their aqueous solutions was studied using biosurfactants as collectors. For recovering the isoflavones from the soy whey wastewater, a two-stage batch foam fractionation was developed using the soy proteins as collectors. The results showed that when the conditions of the first stage were temperature of 60°C, pH of 5.0, volumetric air flow rate 80 of mL/min, and loading liquid volume of 400 mL, a high isoflavones enrichment ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The production of low-clinker and zero-clinker cements is noteworthy. They can be obtained from the waste [12][13][14][15] containing calcium oxides. The decarbonization process was realized in the previous production.…”
Section: Comparative Indicators For the Release Of Carbon Dioxide In mentioning
confidence: 99%
“…The production of low-clinker and zero-clinker cements is noteworthy. They can be obtained from the waste [12][13][14][15] containing calcium oxides. The decarbonization process was realized in the previous production.…”
Section: Comparative Indicators For the Release Of Carbon Dioxide In mentioning
confidence: 99%
“…Foam fractionation was performed to concentrate isoflavones from the soy whey wastewater under the suitable conditions of temperature 60°C, pH 5.0, volumetric air flow rate 80 mL/min and loading liquid height of 400 mm [9]. The enrichment ratio of isoflavones was 4.05.…”
Section: Enrichment Of Isoflavones From the Soy Whey Wastewater Usingmentioning
confidence: 99%
“…Our previous work has indicated that isoflavones can be effectively concentrated from the soy whey wastewater using foam fractionation, in which whey soy proteins (WSP) are used as the collectors [9]. In order to obtain highly purified isoflavones, it is significant to isolate WSP from isoflavones in the foamate.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In spite of everything, methylene blue is surely one of the most used dye in textile industries and, for this reason, the developing of new strategies for the efficient removal from water effluents is still ongoing and of great interest. [22][23][24][25][26][27] The common methods for the removal of organic dyes include: chemical oxidation or reduction, 28 precipitation, 29 ion exchange, 30 electrolysis, 31 photo-catalytic processes, 32,33 membrane ltration, 34 ozonation, 35 degradation, 36 bio-sorption 37 and adsorption. 38,39 In particular, adsorption is one of the most used techniques because it relies on a simple mechanism, does not produce handling problems, and the process can be reversible.…”
Section: Introductionmentioning
confidence: 99%